1998
DOI: 10.1530/eje.0.1390231
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin receptor subtypes in the microvillous trophoblastic membrane of early gestation and term human placentas

Abstract: The 125 I-labeled endothelin-1 ([ 125 I]ET-1) binding sites in microvillous membranes from early gestation and term human placentas were investigated. The K d s for [125 I]ET-1 binding to early gestation (68 Ϯ 15 pmol/l) and term (45 Ϯ 8 pmol/l) microvilli (n ¼ 4) were not significantly different. The density of binding sites decreased significantly, from 243 Ϯ 80 fmol/mg protein in early gestation microvilli to 54 Ϯ 10 fmol/mg protein in term microvilli. The endothelin (ET) receptor (ET-R) subtype profiles we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…ET-1 clearance is mediated via the ETB receptor. 42 A study by Mondon et al 43 found that the ETB receptor is expressed in term placental microvilli and suggested that the ETB receptor on the placental microvillous membrane may play a major role in ET-1 clearance by modulating the amounts of ET-1 in the maternal intervillous blood space. Given that the microvillus plasma membrane of the human placental syncytiotrophoblast is in direct contact with maternal blood (or the maternal perfusate in our model), this would be a source of ETB receptor-mediated ET-1 clearance, which might explain the reduction in ET-1 levels over time.…”
Section: Hypoxia In Human Placental Perfusionmentioning
confidence: 99%
“…ET-1 clearance is mediated via the ETB receptor. 42 A study by Mondon et al 43 found that the ETB receptor is expressed in term placental microvilli and suggested that the ETB receptor on the placental microvillous membrane may play a major role in ET-1 clearance by modulating the amounts of ET-1 in the maternal intervillous blood space. Given that the microvillus plasma membrane of the human placental syncytiotrophoblast is in direct contact with maternal blood (or the maternal perfusate in our model), this would be a source of ETB receptor-mediated ET-1 clearance, which might explain the reduction in ET-1 levels over time.…”
Section: Hypoxia In Human Placental Perfusionmentioning
confidence: 99%
“…In addition to its steroidogenic activity, the placenta also biosynthesizes the polypeptide hormones endothelin-1 and -3, which are presumed to exert both autocrine and paracrine effects in placental tissue (16,45). Endothelin receptors are present on fetal vessels, on both mem-branes of the syncytiotrophoblast, and on extravillous cytotrophoblasts (16,39). Secretion of endothelin-1 from trophoblastic cells in culture has been demonstrated (6).…”
Section: R1499mentioning
confidence: 99%
“…ET A is located primarily on the uterine endometrial stromal cells and ET B on glandular epithelium. 23 While both ET A and ET B are expressed in the human placenta, ET B predominates throughout gestation, 24,25 in contrast to the greater abundance of ET A in the rat. In the human, ET A increases near term and is the primary ET-1 receptor in stem villi vessels, whereas ET B expression is more prominent in peripheral vessels and in the decidua and does not change during gestation.…”
Section: Discussionmentioning
confidence: 99%
“…In the human, ET A increases near term and is the primary ET-1 receptor in stem villi vessels, whereas ET B expression is more prominent in peripheral vessels and in the decidua and does not change during gestation. [24][25][26] Both ET-1 and ET-3 are produced in placental stem villi vessels, the primary site of placental vascular resistance. 27 ET-1 acting via ET A receptors, then, may cause vasoconstriction leading to placental ischemia in the human, corresponding with what we have reported in NOS inhibition-induced fetal growth restriction as well as in hypoxia-induced fetal growth restriction in the rat.…”
Section: Discussionmentioning
confidence: 99%